2020
DOI: 10.1002/symb.484
|View full text |Cite
|
Sign up to set email alerts
|

“We're the Show at the Circus”: Racially Dissecting the Multiracial Body

Abstract: This work illustrates how the meaning and consequence of multiraciality are formed within a racialized interaction order. Drawing from 76 interviews with single-race and multiracial online daters, I argue that online daters reinforce racialized and gendered categorical differences through their examination of the mixed-race body. I refer to this process as "multiracial dissection," an intersubjective racialization process that invests bodies with racial and gendered meanings. Multiracial dissection may lead to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Post hoc comparisons between each racial group using Fisher's least significant difference method (Armstrong, 2014) showed that participants viewed the Black/White mixed‐race targets longest, had more fixations, and more revisits to their AOIs than other targets. Participants' higher number of revisits to mixed‐race women's AOIs offers empirical evidence that people look at mixed‐race bodies as discrete physical features that are considered ‘racial contradictions,’ such as ‘light eyes and dark skin or freckles and curly hair,’ which Curington theorized as multiracial dissection (Curington, 2021, p. 272; Haritaworn, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Post hoc comparisons between each racial group using Fisher's least significant difference method (Armstrong, 2014) showed that participants viewed the Black/White mixed‐race targets longest, had more fixations, and more revisits to their AOIs than other targets. Participants' higher number of revisits to mixed‐race women's AOIs offers empirical evidence that people look at mixed‐race bodies as discrete physical features that are considered ‘racial contradictions,’ such as ‘light eyes and dark skin or freckles and curly hair,’ which Curington theorized as multiracial dissection (Curington, 2021, p. 272; Haritaworn, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, parents of Multiracial‐Black youth might tailor messages to the gender of the children (Ortiz, 2017). Multiracial‐Black girls, for instance, may hear more messages than boys about coping with social exclusion and hypersexualization due to the intersection of their race and gender (Curington, 2021; Rockquemore & Laszloffy, 2005). Therefore, researchers should examine how child gender influences the racial socialization that youth receive and understand that messages from any domain can be gendered (Brown et al, 2017; Thomas & King, 2007).…”
Section: The Multiracial‐black Socialization Modelmentioning
confidence: 99%
“…Scholars have argued that sharing a distinct, non-dominant identity can cultivate a bond that inspires a powerful, honest conversation (Johnson-Bailey, 2004). A shared multiracial identity might be particularly relevant in multiracial research as participants discuss hostile interactions with monoracial people (Harris, 2016;Waring, 2023) or espouse uncritical beliefs that frame multiracial people as superior (Curington, 2020;Waring, 2013), especially those who are part-white (Gay et al, 2022), which they might be less likely to share if the researcher were monoracial. Additionally, a common identity can offer validation via "a knowing of [t]he[i]r emotional experience," especially when participants' views challenge social norms (Ross, 2017, p. 329).…”
Section: Recruitment and Reflexivitymentioning
confidence: 99%
“…2021; Franco et al, 2020;Gay et al, 2022), among friends and peers (Johnston & Nadal, 2010;Jones & Rogers, 2022;Waring, 2017), with romantic partners (Curington, 2020;Waring, 2013), in school (Harris, 2016;Ingraham et al, 2014;Mohajeri, 2022) and at work (Harris, 2020;Hernández, 2018). These inequitable experiences demonstrate how parents, teachers, partners, and coworkers often marginalize multiracial people by constructing a monoracial background as the "norm or ideal" and framing a multiracial background as "substandard or different" (Johnston & Nadal, 2010, p. 127).…”
mentioning
confidence: 99%